2019
DOI: 10.1111/eea.12840
|View full text |Cite
|
Sign up to set email alerts
|

Potential host fruits for Drosophila suzukii: olfactory and oviposition preferences and suitability for development

Abstract: Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), the spotted wing drosophila, is a pest endemic to Southeast Asia that invaded the Americas and Europe in 2008. In contrast to most of its congeners, D. suzukii possesses a serrated ovipositor that allows it to lay eggs in unwounded commercial fruits, resulting in severe revenue losses for the industry. The purpose of this study was to determine the susceptibility of known host fruits, including cherry, strawberry, blueberry, and grape, and potential host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
(58 reference statements)
0
17
1
Order By: Relevance
“…Grapevine can be a host plant for this pest [12][13][14][15] and damage has been found in European countries on different white and black grape cultivars 16,23,24 . On the other hand, studies conducted by Lee et al 13 , Bellamy et al 26 and Cai et al 38 found low attraction for grapes, suggesting that D. suzukii may prefer fruit with a thin skin. In addition, laboratory studies on grape berries reported low oviposition, slow developmental rates and limited survival to the adult stage 13,[17][18][19] .…”
Section: Discussionmentioning
confidence: 93%
“…Grapevine can be a host plant for this pest [12][13][14][15] and damage has been found in European countries on different white and black grape cultivars 16,23,24 . On the other hand, studies conducted by Lee et al 13 , Bellamy et al 26 and Cai et al 38 found low attraction for grapes, suggesting that D. suzukii may prefer fruit with a thin skin. In addition, laboratory studies on grape berries reported low oviposition, slow developmental rates and limited survival to the adult stage 13,[17][18][19] .…”
Section: Discussionmentioning
confidence: 93%
“…Given that D. suzukii females prefer to oviposit on fruit with high sugar concentrations due to their nutritional benefit 7 , we expected female oviposition preference for anthracnose-infected fruits (hypothesis 1). However, D. suzukii also prefers ovipositing on ripe fruit in which sugar concentrations are typically lower than in rotten fruit 48 . It is, thus, likely that D. suzukii oviposition preference is not determined solely by the sugar content in fruits 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Since its arrival to the continental United States in 2008, Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) has disrupted Integrated Pest Management (IPM) programs across major U.S. fruit-growing regions [ 9 ]. Although D. suzukii accepts a broad spectrum of hosts and ripeness, females often use their sawlike ovipositor to lay eggs into soft-skinned, ripening and ripe fruit including blueberries, caneberries, strawberries, and cherries [ 10 , 11 , 12 , 13 , 14 ]. Their short reproductive cycle and quick development allows populations to grow rapidly and makes management extremely difficult [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%